Analysis of Underage Motorcycle-Riding Behavior from the Perspective of Social Bond Theory - Rizza Armelvia Sari; Khairunnisa Khairunnisa; Retno Wahyuningtyas (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2026)
Underage motorcycle riding has become a persistent social and road-safety problem in Padang Sarai Urban Village, Koto Tangah District, Padang City, despite legal age and licensing requirements. This study examines the phenomenon through Travis Hirschi’s Social Bond Theory, focusing on attachment, commitment, involvement, and belief. A qualitative descriptive design was employed as the primary approach, supported by descriptive quantitative data. Primary data were collected through observation, in-depth interviews, and closed-ended questionnaires, while secondary data were obtained from relevant documents and literature. Informants were selected purposively, and questionnaires were distributed to 98 respondents drawn from 6,369 households using the Slovin formula with a 10% margin of error. Qualitative data were analysed through data condensation, data display, and conclusion drawing, whereas questionnaire responses were analysed using frequencies and percentages. The findings indicate that underage motorcycle riding is sustained by weak emotional attachment between children and parents, low commitment to rules and future consequences, limited involvement in constructive activities, strong peer influence, and weak belief in legal and social norms. Parental busyness, permissive family practices, community tolerance, and the normalisation of underage riding further weaken social control. The study concludes that this behaviour is not merely an individual traffic violation but a socially embedded form of deviance. Strengthening parental supervision, family communication, positive youth activities, legal socialisation, and coordinated community control is essential to reduce underage motorcycle use.